Effect of cross inclined bars on the behaviour of shear wall – floor slab joint under lateral cyclic loading - Greeshma, S.; Jaya, K.P. (Journal of Structural Engineering, 2024)
The main objective of the study is to investigate the effect of extending the slab reinforcement as cross inclined bars at the joint on the behaviour of exterior shear wall – floor slab joint. The connection between slab and shear wall is an essential link in the lateral load resisting mechanism of slab - wall systems. The performance of the connection can influence the pattern and distribution of lateral forces among the vertical elements of the structure. From the literature reviewed it is clear that paucity of information exists in the area of detailing of shear wall to slab connection. Hence an attempt has been made to understand the behaviour of the connection with respect to conventional and non-conventional detailing in order to provide an integral and better performing structural system. The study of the behaviour of joints is of paramount importance in the seismic resistance of structures. To analyze such behaviour it requires modeling of materials, modeling of the structure and also modeling of the loading. The fi nite element analysis will probably be the best choice to incorporate the variations in the above parameters. Considering the capabilities of the software package ANSYS, the same was adopted for the present work. The analysis includes modeling of exterior shear wall- slab joint with conventional and non-conventional reinforcement detailing. The analytical investigations were carried out in order to provide information to the designer about (i) Ultimate Load and Moment Carrying Capacity, (ii) Joint displacement ductility, and (iii) Load – Displacement Hysteretic Loops and Energy Dissipation.